Teknik Permainan Kelompok untuk Meningkatkan Perkembangan Sosial Emosional Anak - Delis Nurmilasari; Evi Afiati; Putri Dian Dia Conia (Journal of Education and Counseling (JECO), 2021)
This study aims to answer whether the application of group games can improve children's social emotional development. This study uses pre-experimental research techniques with one group pre-test post-test design. The method of data collection in the study used an observation instrument. The research subjects consisted of 8 students who had not optimal social-emotional development. The results showed that the socio-emotional development of children in TKQ MALNU increased after being given treatment with group games. Based on the results of the average pre-test and post-test, there is an average difference of 0.74 which defines that group games are effective for improving the social emotional development of children in TKQ MALNU.